Effects of childcare disagreement with children, social support, and health status on unmet healthcare-seeking behavior among the migrant older with children to Jinan, China - Shi, Xinfei; Zong, Di; Lu, Zhongqian; Li, Shixue; Kong, Fanlei (Frontiers in Public Health, 2022)
As the acceleration of China's urbanization, the number of the migrant elderly following children (MEFC) continued to increase. This study aimed to clarify the effects of childcare disagreement with children, social support and health status on unmet healthcare seeking behavior among the MEFC to Jinan, China. A cross-sectional study included 656 MEFC (36.3% male, 63.7% female) by employing multi-stage cluster random sampling in Jinan, China. Social support was assessed using the Social Support Rating Scale. Descriptive analysis, chi-squared test and binary logistic regression were applied to analyze the association between childcare disagreement with children, social support, health status and unmet healthcare seeking behavior of the MEFC. 41.3% of the participants had unmet healthcare seeking behavior. Logistic regression analysis showed that the MEFC with a household monthly income of CNY≥2501, whose health status compared to last year get better were more likely to have unmet healthcare seeking behavior; while the female, with partially will of migration, hired a nanny, had smaller childcare disagreement with children on dressing, had smaller childcare disagreement with children on consumption, had moderate social support were less likely to experience the unmet healthcare seeking behavior. Recommendations to government and family members for improving the health services seeking behavior of MEFC were given.